Pregnant women's hepatitis B vaccination coverage in Nigeria: a national pilot cross-sectional study - George Uchenna Eleje; Godwin Otuodichinma Akaba; Ikechukwu Innocent Mbachu; Ayyuba Rabiu; Olabisi Morebise Loto; Hadiza Abdullahi Usman; Preye Owen Fiebai; Rebecca Chinyelu Chukwuanukwu; Ngozi Nneka Joe-Ikechebelu; Chike Henry Nwankwo; Stephen Okoroafor Kalu; Chinyere Ukamaka Onubogu; et al. (SAGE Publishing, 2021)
Objective: To determine the hepatitis B vaccination coverage, full-dose (⩾3) coverage and the associated factors affecting uptake among pregnant women. Methods: This was a cross-sectional study among pregnant women attending antenatal care in six tertiary hospitals across all the geopolitical zones of Nigeria. Pregnant women who consented to the study completed screening questions about their hepatitis B vaccination status and coverage. The main outcome measures were hepatitis B vaccination coverage rate, dose, and factors affecting uptake. Bivariate analysis was performed by the chi-square test and conditional logistic regression analysis was used to determine variables associated with uptake of the vaccination. Odds ratios (ORs) and adjusted odds ratios (aORs) were calculated and statistical significance was accepted when p -value was < 0.05. Results: Of 159 pregnant women who completed the interview questions, 21 [13.2%, 95% confidence interval (CI) 7.9-18.5%] were vaccinated for hepatitis B for one to three doses. The numbers of doses received were: three doses (8/159, 5.0%), two doses (5/159, 3.1%), and one dose (8/159, 5.0%). The reasons for non-uptake of vaccination included: lack of awareness of the vaccine 83/138 (60.1%), inadequate access to vaccine 11/138 (8.0%), and positivity to hepatitis B virus 10/138 (7.2%). The uptake of hepatitis B vaccination was significantly affected by the level of education (OR 0.284, 95% CI 0.08-1.01, p  = 0.041), but in multivariable logistic regression, adjusted for confounders, the association between hepatitis B vaccination and participants' level of education (aOR 3.09; 95% CI 0.95-10.16; p  = 0.061) did not remain significant. Conclusions: In Nigeria, the national hepatitis B vaccination coverage among pregnant women appears poor, with the full-dose coverage even poorer. The level of education was not positively associated with uptake of hepatitis B vaccination, while lack of awareness of the vaccine was the commonest reason for non-uptake. Funding: TETFund National Research Fund 2019 (grant number TETFund/DR&D/CE/NRF/STI/33).